The Role of Social Capital in Shaping Export Capability: The Influence of Education and Empowerment on Export Clinic MSMEs in Surakarta - Kurniawati, Nadya; Sunesti, Yuyun; Sakuntalawati, LV Ratna Devi (Ilomata International Journal of Social Science, 2025)
MSMEs (Micro, Small and Medium Enterprise) are vital to Indonesia's economy, driving employment, income, and poverty reduction. However, their global expansion potential remains underutilized due to challenges in accessing international markets, highlighting the need for strategies to boost their export capabilities and competitiveness. This study analyses the influence of education level, empowerment, and social capital on the export performance of MSMEs participating in Surakarta's Export Clinic Technical Guidance program. This study used a quantitative approach with a descriptive research design and path analysis to test the influence of variables. The research sample consisted of 60 MSME actors involved in the export clinic program in Surakarta. The analysis results indicate an indirect relationship between education level and MSME export capability through social capital, and there is an indirect relationship between empowerment level and export capability through social capital, with a better understanding of the global market and marketing techniques that support their competitiveness. Findings show that education provides a better understanding of the global market and marketing techniques that support their competitiveness. Empowerment of MSMEs through training and mentoring has been shown to increase self-confidence and technical skills, which are important in facing export challenges. Social capital, which includes networks and relationships with external parties, is important in expanding access to international markets. These findings suggest that combining these factors can strengthen the export capability of MSMEs in Surakarta.